1999
DOI: 10.1128/jb.181.23.7308-7313.1999
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for a New Bacteriophage of Borrelia burgdorferi

Abstract: We have recovered a DNase-protected, chloroform-resistant molecule of DNA from the cell-free supernatant of a Borrelia burgdorferi culture. The DNA is a 32-kb double-stranded linear molecule that is derived from the 32-kb circular plasmids (cp32s) of the B. burgdorferi genome. Electron microscopy of samples from which the 32-kb DNA molecule was purified revealed bacteriophage particles. The bacteriophage has a polyhedral head with a diameter of 55 nm and appears to have a simple 100-nm-long tail. The phage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 47 publications
(72 reference statements)
5
70
0
Order By: Relevance
“…Despite the fact that, at the lysogenic stage, the genomes of temperate bacteriophages are generally integrated into the bacterial chromosome, there are some prophages that replicate as plasmids, e.g. the E. coli phages P1 (Ikeda and Tomizawa, 1968), P4 (Briani et al, 2001) and N15 (Ravin and Shulga, 1970), phage cp32 from Borrelia burgdorferi (Eggers and Samuels, 1999) and the Leptospira biflexa phage LE1 (Saint Girons et al, 2000). Unlike the other aforementioned phages, the N15 prophage is unique in that it is a linear plasmid with covalently closed ends (Rybchin and Svarchevsky, 1999;Ravin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that, at the lysogenic stage, the genomes of temperate bacteriophages are generally integrated into the bacterial chromosome, there are some prophages that replicate as plasmids, e.g. the E. coli phages P1 (Ikeda and Tomizawa, 1968), P4 (Briani et al, 2001) and N15 (Ravin and Shulga, 1970), phage cp32 from Borrelia burgdorferi (Eggers and Samuels, 1999) and the Leptospira biflexa phage LE1 (Saint Girons et al, 2000). Unlike the other aforementioned phages, the N15 prophage is unique in that it is a linear plasmid with covalently closed ends (Rybchin and Svarchevsky, 1999;Ravin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The telomeric repeats of several B. burgdorferi linear plasmids and the linear chromosome are highly similar (Casjens et al, 2000), possibly acting as sources of homology for recombination, reminiscent of antigenic variation in lower eukaryotes (Donelson, 1995;Hernandez-Rivas et al, 1997). Recently, Eggers and Samuels (1999) reported that some members of the ubiquitous family of 32 kb circular plasmids (cp32) are prophage genomes, suggesting a potential method of horizontal gene transfer among Borrelia. Reflecting the essential nature of plasmids to B. burgdorferi, Barbour (1993) proposed that the extrachromosomal elements be referred to as minichromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Moreover, enhanced expression of the PHB degradation gene (phaZ) relative to that of the synthetic gene (phaC) reportedly led to R-3HB secretion into the medium without PHB accumulation. [14] These studies indicate that R-3HB is produced and secreted from PHB www.advancedsciencenews.com www.biotechnology-journal.com dependent and independent pathways under aerobic conditions (Figure 3). In agreement, R-3HB was produced independently of PHB via two pathways allowing NADPH-dependent using acetoacetyl-CoA as a precursor.…”
Section: Discussionmentioning
confidence: 92%
“…However, there is a possibility that S-isomer is generated by the decomposition of PHB and then the optical purity is decreased. [14] The decomposition of PHB in wild-type bacterial cells is used to obtain R-3HB in a variety of different conditions. [5,15,19] Therefore, we need to pay attention to the optical purity of the product generated by microorganisms.…”
Section: Analysis Of Optical Puritymentioning
confidence: 99%